Using Hydrogen Peroxide for Rocket Fuel Tank Pressurization: Innovations, Advantages, and Challenges - Mykhailo Vorobei; Mykola Bondarenko (Challenges and Issues of Modern Science, 2024)
This paper explores the innovative use of hydrogen peroxide (H₂O₂) as a pressurizing agent for rocket fuel tanks, highlighting its potential to enhance efficiency and performance in rocket propulsion systems. The study delves into the thermodynamic and chemical properties of H₂O₂, emphasizing its advantages over traditional pressurizing methods such as nitrogen and helium. Key benefits include higher energy density, cost efficiency, and environmental safety, as H₂O₂ decomposes into water and oxygen. The paper also addresses significant technical and operational challenges, including safety concerns, material compatibility, and heat management. Through case studies and recent experimental data, the paper illustrates successful applications and practical solutions. Future research directions focus on improving catalyst efficiency, developing advanced materials, and integrating H₂O₂ systems with hybrid and liquid rocket engines. This comprehensive analysis underscores H₂O₂'s potential to revolutionize rocket fuel tank pressurization, paving the way for more efficient and sustainable space exploration technologies.